Regional variation and changes in competencies of BRAC graduates and their enrollment status in formal schools - Imam, Syeda Rumnaz; Nath, Samir Ranjan (BRAC Research and Evaluation Division (RED), 2020)
This study aimed at examining the regional variation and changes in basic competency and enrolment rate of BRAC graduates. This is a secondary analysis of Nath's study on assessing the level of basic competencies of BRAC graduates in 1995 and 1997. Significant regional variation and changes in the level of basis competency and enrolment rate were observed. It was evident that in both the years competency level of the graduates of eastem region was significantly more poor than that of the other regions. Competency level of the graduates of southern region has decreased significantly in 1997. Regional variation was the second most significant predictor of enrolment status of BRAC graduates of 1997 but it had no significant effect on enrolment rate in 1995. In 1997, enrolment rate of the graduates of central region was significantly lower than that of the other regions and was higher in the northern region. Enrollment rate of the graduates of central region decreased in 1997. Male enrolment in eastern region was significantly higher than the female in 1997. This study did not have the adequate data to find the reasons lying behind regional variation and changes in competency level of BRAC graduates. Further study is needed to identify the reasons.